High-resolution taphonomy and sequence stratigraphy of internally complex, bakevelliid-dominated coquinas from the Aptian Romualdo Formation, Araripe Basin, NE Brazil - Rodrigues, M. G. [UNESP]; Varejao, F. G.; Matos, S. A. [UNESP]; Fuersich, F. T.; Warren, L. V. [UNESP]; Assine, M. L. [UNESP]; Simoes, M. G. [UNESP] (Elsevier B.V., 2022)
The Aptian Romualdo Formation (Araripe Basin, NE Brazil) was deposited in a restricted epeiric sea, during the opening of the South Atlantic Ocean, with a coeval record to that in the Brazilian Pre-Salt succession. The upper part of the Romualdo Formation encompasses the Highstand Systems Tract of a third-order stratigraphic sequence, and contains shell beds interbedded with shale, siltstone, and fine-grained sandstone. Based on distinct taphonomic features (shell sorting, fragmentation, abrasion, rounding, and orientation), sedimentological criteria (shell abundance, type of matrix, sedimentary structures, and presence/absence of quartz grains), and stratigraphic attributes (bed thickness, geometry, contacts), the paleoenvironmental conditions and the bed-bybed accumulation history of the coquinas is disentangled. Eight carbonate microfacies were recognized, including ostracod carbonate mudstone, bivalve-gastropod wackestone, gastropod-bivalve packstone, bivalvegastropod grainstone, bivalve-gastropod floatstone, bivalve-gastropod rudstone, bakevelliid floatstone, and bakevelliid rudstone, which are organized in six, cm-thick shell concentrations. Mudstone and wackestone facies mark the settling of carbonate muds without significant bottom currents and wave action, probably below storm wave base, whereas packstone, floatstone, and rudstone, with fragmented, rounded, and oriented shells, were deposited in agitated waters, between the fair-weather and the storm wave bases. Ripple cross-laminated grainstone is interpreted as high-energy facies deposited above fair-weather wave base. The shell beds are internally complex and consist of cm-scale alternations of microfacies differing in packing, sorting, and composition. They tend to fine upwards within dm-thick shell beds, generating shallowing-upward facies sequences. The concentrations, the uppermost one with in situ bakevelliid shells in the top, record high-frequency base level oscillations influenced by eustasy and climate changes. These bioclastic accumulations originated by the superposition of sedimentologic and primary biologic processes (e.g., post-deposition meiofaunal bioturbation). The cm-thick, low-diversity shell beds are excellent examples of multiple-event carbonate deposits generated in a siliciclastic-dominated, restricted epeiric sea, revealing high-frequency cycles in proximal to distal restricted marine settings.
Keywords: Epeiric sea coquinas; Multi-event shell beds; High-resolution sequence stratigraphy; Lower cretaceous